A armadilha do paradoxo de tostines: Financiamentos do BNDES por porte de empresas e seu potencial na transformaç\~ao estrutural das microrregi\~oes do Brasil - Felipe Orsolin Teixeira; Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The study aimed to investigate the potential spatial correlation between BNDES funding allocation across different company sizes and the structural transformation of micro-regions in Brazil. Economic complexity indices, both linear and non-linear, along with productivity in foreign trade, were utilized as proxies for measuring structural transformation in this context. The period used was from 2009 to 2020. The data indicated that the majority of BNDES resources for the manufacturing industry are destined for the South and Southeast regions and, mainly, for micro-regions that are home to large commercial centers. A low-low pattern (low financing intensity and low complexity) was also observed for the microregions in the central part of the country. On the other hand, the econometric results showed the existence of spatial spillover effects of BNDES financing for microenterprises in the structural transformation of the country's microregions.
Keywords: L6; O4; R1; 330; BNDES; company size; microregions; economic complexity